A Critical Review of the Indonesian Council of Ulama (MUI) Fatwa Towards Increasing Sharia Financial Literacy (Systematic Literature Review) - Soumena, Fadly Yashari (Journal of Economics Research and Social Sciences, 2024)
This research aims to conduct a critical review of the improvement of Islamic financial literacy based on the Fatwa of the Indonesian Ulama Council (MUI). The main issues reviewed are the controversies surrounding Islamic economics and the importance of financial literacy in the context of sharia. The research method used is Systematic Literature Review (SLR) using the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) framework to guide the research process. The results of this study indicate that Islamic financial literacy has a very important role in understanding and managing finances wisely in the context of sharia. The data synthesis result of this study shows that the Indonesian Ulama Council (MUI) Fatwa contributes indirectly to the improvement of Islamic financial literacy in Indonesia. MUI Fatwa is used as one of the main indicators in explaining Islamic financial literacy through financial institutions.